IRON DEFICIENCY ANAEMIA -A RISK FACTOR FOR FEBRILE SEIZURES IN CHILDREN - Sherjil, Ahmad; Saeed, Zaheer us; Shehzad, Sohail; Amjad, Rabia (Journal of Ayub Medical College Abbottabad, 2010)
Background: Iron deficiency anaemia and febrile seizures are two common diseases in children worldwide as well as in our country. Iron insufficiency is known to cause neurological symptoms like behavioural changes, poor attention span and learning deficits in children. Therefore, it may also be associated with other neurological disturbances like febrile seizures in children. Objective of our casecontrol study was to find association between iron deficiency anaemia and febrile seizures in children. Methods: This multicentre study was conducted in Department of Paediatrics HIT Hospital Taxila Cantt, Department of Paediatrics CMH Mangla and Department of Paediatrics POF Hospital Wah Cantt, from June 2008 to June 2010. Three hundred and ten children aged between 6 months to 6 years were included in the study. One hundred and fifty-seven children who presented with febrile seizures were our cases, while, 153 children who presented with febrile illnesses without seizures were recruited as controls. All patients were assessed for iron deficiency anaemia by measuring haemoglobin level, serum ferritin level, Mean Corpuscular Haemoglobin Concentration (MCHC) and Mean Corpuscular Volume (MCV). Patients with iron deficiency anaemia amongst controls and cases were documented. Percentages and Odds ratio were derived from the collected data. Results: 31.85% of cases (50 out of 157) had iron deficiency anaemia whereas, 19.6% of controls (30 out of 153) were found to have iron deficiency anaemia as revealed by low levels of haemoglobin level, serum ferritin level, Mean Corpuscular Haemoglobin Concentration and Mean Corpuscular Volume. Odds ratio was 1.93. Conclusion: Patients with febrile seizures are 1.93 times more likely to have iron deficiency anaemia compared to febrile patients without seizures. Keywords: Iron Deficiency Anaemia, Febrile Seizures, Serum Ferritin, Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin Concentration (MCHC)